Minimally invasive treatments for benign prostatic enlargement: systematic review of randomised controlled trials. (9th October 2008) - Lourenco, Tania; Pickard, Robert; Vale, Luke; Grant, Adrian; Fraser, Cynthia; MacLennan, Graeme; N'Dow, James
Abstract : Objective To compare the effectiveness and risk profile of minimally invasive interventions against the current standard of transurethral resection of the prostate. Design Systematic review and meta-analysis of randomised controlled trials. Data sources Electronic and paper records up to March 2006. Review methods We searched for all relevant randomised controlled trials. Two reviewers independently extracted data and assessed quality. Meta-analyses of prespecified outcomes were performed with fixed and random effects models and reported using relative risks or weighted mean difference. Results 3794 abstracts were identified; 22 randomised controlled trials met the inclusion criteria. These provided data on 2434 participants. The studies evaluated were of moderate to poor quality with small sample sizes. Minimally invasive interventions were less effective than transurethral resection of the prostate in terms of improvement in symptom scores and increase in urine flow rate, with most comparisons showing significance despite wide confidence intervals. Rates of reoperation were significantly higher for minimally invasive treatments. The risk profile of minimally invasive interventions was better than that of transurethral resection, with fewer adverse events. The results, however, showed significant heterogeneity. Conclusion Which minimally invasive intervention is the most promising remains unclear. Their place in the management of benign prostate enlargement will continue to remain controversial until well designed and well reported randomised controlled trials following CONSORT guidelines prove they are superior and more cost effective than drug treatment, or that strategies of sequential surgical treatments are preferred by patients and are more cost effective than the more invasive but more effective tissue ablative interventions such as transurethral resection.